2019
DOI: 10.46660/ijeeg.vol10.iss3.2019.321
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Degradation, Quality of Institutions and Tourism: New Evidence from Pakistan

Abstract: This study explores the effects of tourism, quality of institutions and FDI on environmental degradation inPakistan for the two time periods i.e. 1996-2017 and 2000-2017. Quality of institutions is included in the time period2000-2017 which is adopted from world governance indicators but due to lack of the data it has not been included insecond time (1999-2017). To find out the relationship among given variables, Ordinary Least Square (OLS) regressionwas carried out, moreover, Breusch-Godfrey Serial Correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The outcomes of the PLSM has revealed that CPEC does not contribute to climate change in contrast to the research of (Ali, 2018;Saad, Xinping & Ijaz, 2019) who argues that environmental pollution is the main concerned of CPEC projects. However, the study results are consistent with (Sekrafi & Shgaier, 2018, Muhammad et. al, 2019 which also showed that tourism is contributing pollution in Pakistan.…”
Section: Effect Size (F 2 )supporting
confidence: 91%
“…The outcomes of the PLSM has revealed that CPEC does not contribute to climate change in contrast to the research of (Ali, 2018;Saad, Xinping & Ijaz, 2019) who argues that environmental pollution is the main concerned of CPEC projects. However, the study results are consistent with (Sekrafi & Shgaier, 2018, Muhammad et. al, 2019 which also showed that tourism is contributing pollution in Pakistan.…”
Section: Effect Size (F 2 )supporting
confidence: 91%
“…Similarly, the role of energy consumption is also effective and an increase in consumption of energy have significant impact on the pollution in Pakistan. On the other hand, the effect of foreign direct is not significant but its effect is positive increasing the environmental pollution in Pakistan ( Muhammad et al, 2019;Bakhsh et al, 2017). The effect of open trade policies have also psoitive influence on the pollution.…”
Section: Resultsmentioning
confidence: 96%
“…In sum, majority of studies indicated that the growing population is exerting pressure on the demand of natural resources. However, population is not only the key factor of environmental pollution; the other influential factors includes economic growth (Yang and Zhao, 2014;Omri, 2014), tourism (Paramati et al, 2017;León et al, 2014), trade openness (Chebbi et al, 2011;Naranpanawa, 2011 andManagi et al, 2008) and quality of institutions (Muhammad et al, 2019). The current study focused on the population, energy consumption on environmental decay in Pakistan.…”
Section: Introductionmentioning
confidence: 96%